The Role of One’s Motive in Meditation Practices and Prosociality - Reddy, J. Shashi Kiran; Roy, Sisir (Frontiers in Human Neuroscience, 2019)
There exists no individual who does not exhibit prosociality in one or the other situation of their lifetime. But the argument is, to what extent? Whether it arises spontaneously out of true empathy and compassion for others or it is goal-oriented with some hidden motive? Here, our primary intention is to convey that, though various meditation-based interventions can be utilized for different purposes like cultivating prosocial behaviors such as compassion, empathy etc., one's underlying motive and intent seems to play a crucial role in an individual’s development. Most of the studies exploring prosociality in the context of meditation usually do not consider the role of hidden or underlying motivation in one’s prosocial expression. By considering an example of how mindfulness may sometimes lead to wrong consequences, we try to analyze why it is very important to include the aspect of inner motivation in future studies exploring the effects of meditation on prosociality. We also propose that while practicing one may need traditional assistance and ethical/moral teachings in addition to those merely isolated techniques.